Inventory Information System Using LIFO Method: Case Study on Goods Distribution Company Study in Bandung - Saputra, Raka Aditya; Sambani, Egi Badar; Rachman, Rizal; Latif, Dadang; Putra, Yuda Purnama (Informatics Management, Engineering and Information System Journal, 2023)
At one of the goods distribution organizations in Bandung, manual recording problems such as data mistakes, delayed information, and challenges with inventory analysis must be addressed, and here is where the inventory information system comes in. An inventory system must be implemented to improve accuracy and efficiency in inventory management. With the correct technology, the business can reduce data errors, speed up information access, do practical inventory analysis, and increase productivity when taking and maintaining inventory. This study develops a web-based inventory information system using the MySQL database from the XAMPP application, the Laravel framework, and the PHP programming language. Representative data modeling and the creation of user-friendly interfaces are critical components of the design focus, which also considers proper technology selection. In order to better understand user needs and provide answers, system design will use the Object-Oriented Software Engineering (OOSE) model. In order to help with more precise decision-making in inventory management, the Last-In-First-Out (LIFO) method is used in inventory data analysis. Inventory may be easily monitored by using LIFO to offer information on nearly depleted stock and out-of-stock items. One of the Bandung-based goods delivery companies has seen notable gains due to the adoption of the new inventory system. With this new technology, the business may get past problems with manual recording, like data inaccuracies, delayed information, and challenges with inventory analysis. By streamlining the recording process and facilitating more efficient inventory management, this system facilitates better access to inventory information and increases the efficiency of inventory management. In summary, using an inventory system is an excellent way to get around problems with manual goods recording. This solution increases inventory management efficiency and speeds up the recording process for one of the Bandung-based commodities delivery enterprises. Its deployment offers significant advantages, improving the company's overall operating performance and facilitating more effective inventory management.